Instruments to stimulate competition in public procurement: international practice - T. V. Tischenko (Вестник университета)
This article considers the tools used in foreign practice to increase competition and remove restrictions on participation of companies in public procurement. Open competition means that all qualified companies have the right to participate in the public procurement on the basis of fair consideration of their bids and selection of the winner, and the right to appeal. The results of the study have identified the tools that ensure competitiveness of the procurement in foreign practices, are used in the formation of regulatory and legal framework of the contractual system, in bidding, at the stage of contract execution. When bidding procedures are prepared, competition is ensured through the use of a single online platform and exclusion of unreasonable or unnecessary requirements for bidders, except for qualification requirements, which makes it possible to increase attractiveness of the bidding for enterprises and number of participants. At the stage of preparation for the bidding, procuring authorities should analyse the market and form specifications focused on functional criteria for the goods to be supplied to reduce risks of biased selection of the winner. When competitive procedures are held, it is necessary to exclude the possibility of manipulation of criteria for evaluation of proposals and collusion of participants. At the post-contract stage one needs to develop mechanisms to identify possible violations and illegal actions. Based on the results of the study, the indicators that can be used to assess competition of the public procurement in the Russian Federation are formed.